Elimination of nickel ions in a packed column using clamshell waste as an adsorbent - S. Baskar; K. R. Aswin Sidhaarth; L. Mangaleshwaran; Sivarama Krishna Lakkaboyana; Herri Trilaksana; Reddi Mohan Naidu Kalla; Jaewoong Lee; Leonard I. Atanase; Mohsin Kazi; Seepana Praveenkumar (Scientific Reports, 2025)
Abstract The present investigation assessed the viability of utilizing a powdered clam shell in continuous adsorption to eliminate nickel ions from simulated wastewater. The breakthrough curves (BTC) were analyzed by altering the Q (inlet flow rate) in a glass column (ID 5 cm, H 35 cm) with a multi-port and filled with the powdered clamshell adsorbent (PCSA). The PCSA’s nickel adsorption efficiency was maximum (87.68%) with Q = 8 mL/min at a bed length (H) of 25 cm with 1.05 mg/g adsorption capacity. Moreover, the mass transfer zone (MTZ) and idle bed length (Lu) were estimated from the corresponding BTC. The values of MTZ and Lu demonstrated fluctuations in response to changes in bed length, suggesting the presence of non-ideal circumstances. The validity of the Thomas model for predicting column dynamics was established, and the associated model parameters were assessed. Additionally, the parameters of the BDST model were assessed in order to aid in calculating the sufficient depth for a packed bed column (PBC) while scaling up. Therefore, a metal removal process from industrial effluent can be efficiently achieved by utilizing a PBC of powdered clamshell adsorbent.